Anti-Inflammatory, Barrier-Protective, and Antiwrinkle Properties of Agastache rugosa Kuntze in Human Epidermal Keratinocytes. (28th October 2020) - Lee, Yoonjin; Lim, Hye-Won; Ryu, In Wang; Huang, Yu-Hua; Park, Minsik; Chi, Young Min; Lim, Chang-Jin
Abstract : This work aimed to assess the skin-beneficial properties of Agastache rugosa Kuntze, an herbal medication used to treat different types of disorders in traditional folk medicine. The total phenolic compounds and total antiradical, nitrite scavenging, superoxide scavenging, antielastase, and antihyaluronidase activities of a hot water extract of A. rugosa Kuntze leaves (ARE) were spectrophotometrically determined. Intracellular reactive oxygen species (ROS) was fluorometrically quantitated using 2 ′, 7 ′ -dichlorodihydrofluorescein diacetate (DCFH-DA). Inducible nitric oxide synthase (iNOS) and filaggrin were evaluated using Western analysis. Real-time quantitative RT-PCR was used to measure filaggrin mRNA. Caspase-14 activity was determined using a fluorogenic substrate. ARE contained the total phenolic content of 38.9 mg gallic acid equivalent/g extract and exhibited 2, 2 ′ -diphenyl-1-picrylhydrazyl (DPPH) radical, superoxide radical, and nitrite scavenging activities with the SC50 values of 2.9, 1.4, and 1.7 mg/mL, respectively. ARE exerted suppressive activities on nitric oxide (NO) and ROS levels elevated by lipopolysaccharide (LPS) or tumor necrosis factor- α (TNF- α ) in HaCaT keratinocytes. It attenuated the LPS-stimulated expression of iNOS. ARE augmented the UV-B-reduced filaggrin expression on both protein and mRNA levels and was capable of upregulating the UV-B-reduced caspase-14 activity. ARE inhibited in vitro elastase and hyaluronidase activities associated with the wrinkling process. ARE, at the concentrations used, did not interfere with the viability of HaCaT keratinocytes. These findings preliminarily imply that the leaves of A. rugosa possess desirable cosmetic potentials, such as anti-inflammatory, barrier protective, and antiwrinkle activities, which infers their skin healing potentials.